USABILITY TESTING OF BUDI LUHUR UNIVERSITY E-LEARNING SYSTEM USING SYSTEM USABILITY SCALE - Yuwan Jumaryadi; Deni Mahdiana (Jurnal Teknik Informatika (Jutif), 2022)
The usability level of an application is very influential on user satisfaction in using the system. In addition, the usability level is also useful as a starting point for the improvement process of the system being developed. System Usability Scale (SUS) is one of the most widely used testing methods to measure the usability of a system. Users of the Budi Luhur University e-learning system will be given 10 questions and answered on a Likert scale. The results of the calculation of 101 respondents obtained a SUS score of 65.52. This value is in the OK category, but still needs improvement from several aspects such as in terms of user interface and performance. This can be seen from the assessment of the e-learning system that is accessed from the mobile application which gets a score of 41, in contrast to the e-learning system accessed from the website which gets a score of 86. In addition, from the performance of the e-learning system, the score is 77.